2023
DOI: 10.1097/gox.0000000000005311
|View full text |Cite
|
Sign up to set email alerts
|

Free Flap Failure and Complications in Acute Burns: A Systematic Review and Meta-analysis

Julia A. Kasmirski,
Mario Alessandri-Bonetti,
Hilary Liu
et al.

Abstract: Background: Severe acute burn injuries represent a challenge to the reconstructive surgeon. Free flap reconstruction might be required in cases of significant critical structure exposure and soft tissue deficits, when local options are unavailable. This study aimed to determine the free flap complication rate in acute burn patients. Methods: A systematic review and meta-analysis were conducted and reported according to Preferred Reporting Items for Syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 57 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…These are relatively low rates, comparable to free flap loss rates in other populations such as oncological patients, and lower than the rate of flap loss in acute burn patients. [66][67][68] Furthermore, we assessed the rate of contracture recurrence after delayed free flap burn reconstruction and found it to be only 0.62%, which was extremely low. All three contracture recurrences after free flap reconstruction reported in literature occurred in the hand.…”
Section: Discussionmentioning
confidence: 99%
“…These are relatively low rates, comparable to free flap loss rates in other populations such as oncological patients, and lower than the rate of flap loss in acute burn patients. [66][67][68] Furthermore, we assessed the rate of contracture recurrence after delayed free flap burn reconstruction and found it to be only 0.62%, which was extremely low. All three contracture recurrences after free flap reconstruction reported in literature occurred in the hand.…”
Section: Discussionmentioning
confidence: 99%
“…Our group recently conducted a systematic review and meta-analysis of the literature and estimated the absolute risk for free flap failure in acute burns to be around 10%. 3 However, studies have shown flap loss rates as high as 44%. 7 Therefore, further research efforts are necessary to identify factors and solutions that can minimize the risk of flap failure and optimize outcomes for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…33 The simultaneous local and systemic hyperinflammatory response caused by larger burn injuries may contribute to the increased risk of flap failure. 3,4,33 It has been postulated that electrical injuries may be associated with a higher risk of flap loss, but significant differences have not been identified in various studies. [24][25][26] However, conclusions on flap loss differences due to burn etiology are limited due to the low level of evidence and lack of comparative analysis in the available literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations